MỘT SỐ VẤN ĐỀ VỀ MÔI TRƯỜNG VÀ SỬ DỤNG ĐẤT ĐAI TRONG PHÁT TRIỂN GIAO THÔNG ĐÔ THỊ HÀ NỘI - Trung, Nguyễn Vũ (Nhà xuất bản Nông nghiệp, 2016)
Economic development process has created social pressures for Hanoi capital city. A number of environmental and land use issues emerge in urban transport development in Hanoi. Cultural environment and historical value are being destroyed and Hanoi urban landscape being damaged. Traffic congestion, increased pollution, and loss of space function cause waste of time and ineffective labor. To be able to develop an effective urban transport system for Hanoi and to meet requirements of sustainable development, we need to pay attention to the environmental criteria. We need to review the full effects of urban transport development based on historical value, cultural landscapes, and ecological conditions. Urban transportation development planning has to be linked to urban development and associated with urban architecture. Urban transport system must be developed in coordination and development of urban traffic in association with environmental protection and assessment of possible risks that might be caused during transportation development process.